THE EXAMINATION OF BRAND COMMUNITY CONCEPT IN FOOTBALL SPORTS CLUBS AND A CASE STUDY FROM TURKEY: THE EVALUATION OF FENERBAHCE’S SPORTS CLUB AND ITS PRACTICES AS A BRAND COMMUNITY - Muge, Ors; Ozge, Latif (European Scientific Journal, ESJ, 2013)
Today, the concept of brand community is accepted as the highest adaption of consumers to the brands. In this article, the definition of brand community and its basic components are examined conceptually. Afterwards, whether the sports clubs could be addressed as a brand community or not is discussed in the highlight of literature. At the end of the article, Fenerbahce Sports Club (FB) which was first established football club in Turkey with 25 billion fans, is evaluated with its practices as a brand community in a case study.